Incorporation of industrial laundry sludge in the manufacture of particleboards - Rezende, Luciana Cristina Soto Herek; Magalhães, Patrícia de Jesus; Silva, Cynthia Algayer da; Gonçalves, Davana Silva; Bergamasco, Rosângela; Fávaro, Sílvia Luciana (Acta Scientiarum. Technology, 2015)
This study aimed to demonstrate a sustainable alternative to the use of residues by treating industrial laundry wastewater, thereby making them useful in producing wood particleboards as furniture. For this purpose, physical, chemical, and mechanical tests were carried out in order to characterize the product, which showed acceptable characteristics for commercial use as elements in the furniture industry. Â